Exploring customer service experience equity on the customers’ behavioral intention in tourism industry - Hashim, Nurhazirah; Haque, A. K. M. Ahasanul; Abdul Wahab, Abdul Azeez Oluwanisola (2014)

(untitled)
ABSTRACT: Researchers in recent years have begun to pay more attention to the effect of customer experience on consumer behaviors. Many scholars suggested that building "firms must nurture the emotional bonds between the customers and the providers through experiential elements which can fulfill customers’ social and personal needs. In addition, total customer experience is a blend of functional, emotional, branding, and relationship appeals into an integrated business strategy. Besides, understanding customer experience is a crucial for the tourism industry because it is becoming more experience-driven. However, research on the customer service experience equity still lacks a coherent framework and yet requires a lot of development of the framework. To date, past studies on customer service experience equity on the customers behavioral intention are yet not fully been investigated the tourism industry especially in Malaysia. Hence, there is a need to explore the inﬂuence of these values. It is expected that the findings of this study will not only contribute to the contingency theory that customer service experience equity on the customers’ behavioral intention, but also will serves as guideline for policy development by the Ministry of Tourism as it can assist to develop idealistic program for National Tourism Campaign. From the population of customers who experienced and have intention to stay at hotel and resorts, only 400 potential customers from 10 hotel and resorts will be participated in this study. Structural Equation Modeling will be applied to analyze the mentioned relationship. Therefore, this study attempts to investigate the relationship among customer service experience equity towards customers’ behavioral intention.